ANALISIS KINERJA APARATUR PEMERINTAH DALAM PENINGKATAN KUALITAS LAYANAN PUBLIK: (STUDI KASUS PADA GAMPONG LADANG KECAMATAN SUSOH KABUPATEN ACEH BARAT DAYA) - Fina Syafira; Wahyuningsih, Yayuk Eko (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The issue of service to the community is always prominent in the affairs of publiccomplainsh taskthat show, working hours of the apparatur does not comply with therules made pubic difficulty in optaining one.The research is focused to problem of howperformance of village institution in give service to public. And what are the factorsthat influence the task of institution.The research it`s done in Ladang village of Susohsubdistrict Aceh Barat Daya regency, and the research is done by quantitativedescriptive approach. The result showed that the work ethic that is in the staff ofgovernment is not going well, there is a control to village institution and it didn`thappen norm infraction and that values. And punishment that valid in the office is noteffective for the institution.